2005
DOI: 10.1038/sj.mp.4001684
|View full text |Cite|
|
Sign up to set email alerts
|

Stage 2 of the Wellcome Trust UK–Irish bipolar affective disorder sibling-pair genome screen: evidence for linkage on chromosomes 6q16–q21, 4q12–q21, 9p21, 10p14–p12 and 18q22

Abstract: Bipolar affective disorder (BPAD) is a common psychiatric disorder with complex genetic aetiology. We have undertaken a genome-wide scan in one of the largest samples of bipolar affected sibling pairs (ASPs) using a two-stage approach combining sample splitting and marker grid tightening. In this second stage analysis, we have examined 17 regions that achieved a nominally significant maximum likelihood LOD score (MLS) threshold of 0.74 (or 1.18 for the X-chromosome) in stage one. The second stage has added 135… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 43 publications
(41 reference statements)
2
45
1
1
Order By: Relevance
“…With the current set of markers it is impossible to identify in which side of the centromere the susceptibility region for broad mood disorder lies. This linkage finding is consistent with an Irish bipolar disorder sibling pair genome-wide scan, which identified NPL of 2.41 on 9p21-q21 [Cassidy et al, 2007], as well as with an UK-Irish bipolar disorder sibling pair genome-wide scan reporting a multipoint LOD score of 1.74 on 9p21-p12 [Lambert et al, 2005]. Chromosome 9p13 region harbors several interesting candidate genes, including contactin associated protein-like 3 (CNTNAP3) and aldehyde dehydrogenase 1B1 precursor (ALDH1B1) (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With the current set of markers it is impossible to identify in which side of the centromere the susceptibility region for broad mood disorder lies. This linkage finding is consistent with an Irish bipolar disorder sibling pair genome-wide scan, which identified NPL of 2.41 on 9p21-q21 [Cassidy et al, 2007], as well as with an UK-Irish bipolar disorder sibling pair genome-wide scan reporting a multipoint LOD score of 1.74 on 9p21-p12 [Lambert et al, 2005]. Chromosome 9p13 region harbors several interesting candidate genes, including contactin associated protein-like 3 (CNTNAP3) and aldehyde dehydrogenase 1B1 precursor (ALDH1B1) (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Segurado et al [2003] pointed out the highest ranked genetic bin from 9p21 region as providing suggestive evidence for linkage with bipolar disorder (LOD <0.01), as well as McQueen and coworkers identified a suggestive linkage of 2.06 at 9p21.2. In a study of the Wellcome Trust UK-Irish bipolar disorder sibling pair genome-wide scan, Lambert et al [2005] reported a two-point LOD score of 2.02 at 9p21.1. Furthermore, in a genome-wide scan study of bipolar II disorder, Nwulia et al [2007] identified linkage peak of 3.2 at 9p21.3 for nine bipolar II pedigrees (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This indicates our linkage finding for inattention factor is not just another finding of the same linkage of bipolar disorder. More recent stage 2 of the Wellcome Trust UK-Irish bipolar affective disorder sibling-pair genome screen study found some evidence for linkage at two spots on chromosome 10 [Lambert et al, 2005]. One is at 29 cM, which is near to our linkage peak for inattention.…”
Section: Discussionmentioning
confidence: 80%
“…BP [Millar et al, 2007] BP [Lambert et al, 2005] (Continued ) [Xing et al, 2002], I (MDD) [Novak et al, 2006;Tochigi et al, 2008] 6.5…”
Section: 87eà03 Rs10500860mentioning
confidence: 99%